2019
DOI: 10.1158/1535-7163.mct-18-1122
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Sequencing of Adult Glioma

Abstract: Malignant gliomas are a group of intracranial cancers associated with disproportionately high mortality and morbidity. Here, we report ultradeep targeted sequencing of a prospective cohort of 237 tumors from 234 patients consisting of both glioblastoma (GBM) and lower-grade glioma (LGG) using our customized gene panels. We identified 2,485 somatic mutations, including single-nucleotide substitutions and small indels, using a validated in-house protocol. Sixty-one percent of the mutations were contributed by 12… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…Through a survey of more than 45,000 pan-cancer samples, we observed that IDH1 and IDH2 hotspot mutations are uncommon (2%) and extremely rare (0.4%), respectively, in human cancer, a finding in agreement with an independent pan-cancer analysis [37]. Therefore, despite being prevalent in glioma, as reported previously [10,11,14,38], these…”
Section: Discussionsupporting
confidence: 87%
“…Through a survey of more than 45,000 pan-cancer samples, we observed that IDH1 and IDH2 hotspot mutations are uncommon (2%) and extremely rare (0.4%), respectively, in human cancer, a finding in agreement with an independent pan-cancer analysis [37]. Therefore, despite being prevalent in glioma, as reported previously [10,11,14,38], these…”
Section: Discussionsupporting
confidence: 87%
“…In a separate study of 114 matched pre-and post-treatment GBMs, 17 (15%) showed a hypermutator profile at recurrence; among those 17 cases, 16 had mutations in MMR genes, and showed enrichment for MGMT methylation and IDH1 mutation [28]. Others have verified the association between IDH1 mutations and hypermutation after TMZ [15,27,32]. Among 157 pediatric gliomas, only 9 (6%) were hypermutated, and 7 contained mutations in DNA repair genes [14].…”
Section: Discussionmentioning
confidence: 99%
“…According to TCGA data, frequency of EGFR mutation in GBM and LGG is 26.97 and 6.86% respectively. However, recent research has revealed a higher EGFR mutation frequency of 23% in LGGs, attributing to the different population of patients and deeper sequencing depth [38]. It gave us one hint that frequency of EGFR mutation might be notably underestimated, and it also might be the potential explanation of some rapid progressed lower-grade glioma (histopathological diagnosis) which might essentially be higher-grade glioma in molecular level.…”
Section: Discussionmentioning
confidence: 99%